Platelet antibodies in viral hepatitis - Hasdal, Oktay; Özsoylu, Şinasi; Koçak, Nurten (The Turkish Journal of Pediatrics, 1987)
Although antiplatelet antibodies were observed in the sera of 36% and 47% of twenty-five of our subjects with acute hepatitis taken at two week intervals, in which the Handin and Stossel method was used, thrombocytopenia was not documented in any of them.